(untitled) (Comparatismi, 2022)
In this paper, I will present a constellation of three contemporary women writers, three novels and two connected TV series: Elena Ferrante with her My Brilliant Friend cycle (2011-2014), and the homonymous TV series (2018-2022, three seasons directed by Saverio Costanzo, Alice Rohrwacher, and Daniele Lucchetti); Americanah (2013) by Nigerian Chimamanda Ngozi Adichie, and Adichie’s representation of blog inside and outside this novel; The Handmaid’s Tale (1985) by Canadian Margaret Atwood, analyzed from the perspective of the TV series (five seasons directed by Bruce Miller, aired between 2017 and 2022). I will situate this overall constellation in the context of the Global Novel as well as in a transmedia context: two global languages furthermore unified by the common field of contemporary «primordialism» (Appadurai, 140), a gendered trauma of late-modernity. From this shared perspective, I will then focus on the narrative and visual mechanisms of trauma in the three novels and the two TV series.